Kepemimpinan Organisasi dalam Perspektif Psikologi Manajemen: Tinjauan Literatur Sistematis tentang Pengaruh Faktor Psikologis terhadap Kinerja dan Efektivitas Organisasi - Andini Setia Winata; Sherly Margareta; Mu’alimin, Mu’alimin (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Organizational leadership is a crucial factor in determining an organization's success in achieving its stated goals. As leadership develops, studies of leadership emphasize not only managerial aspects but also management psychology approaches that focus on behavior, motivation, and interpersonal relationships within organizations. The complexity of today's organizational dynamics demands that leaders understand the psychological aspects of organizational members in order to improve performance and work effectiveness. Therefore, a literature review on organizational leadership from a management psychology perspective is crucial. This study aims to identify the concept of organizational leadership from a management psychology perspective and the psychological factors that influence leadership effectiveness. The method used is a literature review by searching articles through the Google Scholar database and the Publish or Perish (PoP) application using the keywords organizational leadership and management psychology. The initial search yielded 20 articles, then after a screening and validation process, 16 relevant articles were obtained, and 5 articles were analyzed in depth. The results of the study reveal several key themes in the literature, namely the role of management psychology in organizational leadership, the influence of leadership style on organizational performance, and the importance of psychological factors such as work motivation, communication, and emotional intelligence in enhancing leadership effectiveness. This study concludes that the integration of leadership and management psychology is crucial in creating effective and adaptive organizations. Further research is recommended to empirically examine the relationship between psychological factors and leadership in various organizational contexts.